Effect of temperature and thickness of graphene on the hydrogen storage properties - Huang, Jie (2018)
Hydrogen, of which the application is limited due to the difficulties in finding the ideal storage material, has been considered alternative for petroleum as the main energy source. With its large surface area and other extraordinary physical properties, graphene has been the focus of many researchers as the promising candidate for hydrogen storage and transportation. In this work, the hydrogen storage characteristics of graphene have been investigated by MD simulations. We found that, under the temperature of 70 K and the pressure of 1 MPa, the hydrogen uptake percentage can be as high as 54%. And the majority of the hydrogen atoms are absorbed during the initial 100 – 200 ps of the simulation. Moreover, the hydrogen storage properties of graphene with different environment temperatures have been studied. We found that with increasing temperature, the hydrogen uptake percentage towards the end of the simulation decreases. Furthermore, the number of layers of the graphene sheet also exerts influence of the hydrogen absorption capability of the sample. We conclude that the more graphene sheets are being used, the less hydrogen atoms are being absorbed by the sample. Our work provides insight into optimizing the environmental temperature and thickness of the graphene sheet when designing novel energy storage devices, especially hydrogen storage devices.